767PComparison of chemoradiotherapy (CRT) followed by consolidation with cisplatin and 5-fluorouracil (CF) versus definitive CRT with carboplatin and paclitaxel (CP) in esophageal cancer. (1st October 2019) - Cesca, M G; Pandolfi, N C; Barros, M; de Jesus, V H F; Silva, V S; Camandaroba, M; Felismino, T C; Rodrigues, N; Riechelmann, R P
Abstract: Background: For patients (pts) with esophageal (ES) cancer and fragility or limiting comorbidities resulting in contraindications for surgery, CRT is the only treatment option with curative potential. In this scenario, the best evidence is CRT followed by consolidation chemotherapy based on fluoropyrimidine/platin combination (RTOG 98-01/PRODIGE 5). However, definitive CRT with CP is frequently used due to better tolerance and convenience, despite the lack of phase III trials. Methods: Consecutive frail/comorbid pts with ES cancer were retrospectively selected. Primary objective was to compare response rate (RR) by RECIST 1.1, disease-free survival (DFS) and overall survival (OS) between CRT followed by consolidation with 2 cycles of CF and definitive CRT with weekly CP (carboplatin AUC 2 and paclitaxel 50mg/m 2 ). Radiotherapy dose: 50, 4 Gy. Secondary objectives: prognostic factors and safety. Descriptive statistics were used for population characteristics analysis and Kaplan-Meier curves, Log-Rank Test and Cox Regression for survival analysis. Results: From May, 2010 to May, 2018, 99 pts were treated, 18 (18.2%) with CF and 81 (81.8%) with CP. Median follow-up was 38.7 months (m). 48 (48.5%) were alive at the cut-off date. Median age at diagnosis was 65 (32-86). 72.7% were men. 86.9% had squamous cell carcinoma; 42.4% stage II and 49.5% III. Localization: thoracic (53.3%), abdominal (20.1%), cervical (15.2%) and EGJ (10.1%). General characteristics were well balanced between groups. RR after the CRT phase were similar (CP: 53.1%; CF: 55.5%; p = 0.198). Median DFS was 23.2m (95%CI 5.9-not reached) and 7.2m (95%CI 4.9-9.4) for CF and CP, respectively (HR 0.55; 95%CI 0.29-1.56; p = 0.08). In the multivariate analysis CF was an independent prognostic factor for improved OS (HR 0.36; 95%CI 0.15-0.91; p = 0.03), as were higher body mass index (p = 0.03) and staging (p = 0.04). Rates of major toxicities were similar between the groups. Conclusions: CRT followed by consolidation with CF seems to offer better outcomes than definitive CRT with CP for ES cancer pts not eligible for surgery. Consolidation therapy or type of chemotherapy may have contributed for this difference in outcomes. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.